Increased levels of NETosis biomarkers in high-grade serous ovarian cancer patients’ biofluids: Potential role in disease diagnosis and management - Tomás-Pérez, Sarai; Oto, Julia; Aghababyan, Cristina; Herranz, Raquel; Cuadros-Lozano, Aitor; González-Cantó, Eva; Mc Cormack, Bárbara; Arrés, Judith; Castaño, María; Cana, Fernando; Martínez-Fernández, Laura; Santonja, Núria; et al. (Frontiers in Immunology, 2023)
High-grade serous ovarian cancer (HGSOC) is the second most frequent gynecological malignancy but the most lethal, partially due to the spread of the disease through the peritoneal cavity. Recent evidence has shown that, apart from their role in immune defense through phagocytosis and degranulation, neutrophils are able to participate in cancer progression through the release of neutrophil extracellular traps (NETs) in a process called NETosis. NETs are composed of DNA, histones, calprotectin, myeloperoxidase (MPO) and elastase and the NETosis process has been proposed as a pre-requisite for the establishment of omental metastases in early stages of HGSOC. Nevertheless, its role in advanced stages remains to be elucidated. Therefore, our principal aim is to characterize a NETosis biomarker profile in biofluids from patients with advanced HGSOC and control women. Specifically, five biomarkers of NETosis (cell-free DNA (cfDNA), nucleosomes, citrullinated histone 3 (citH3), calprotectin and MPO) were quantified in plasma and peritoneal fluid (PF) samples from patients (n=45) and control women (n=40). Our results showed that HGSOC patients presented a higher concentration of cfDNA, citH3 and calprotectin in plasma and of all five NETosis biomarkers in PF than control women. Moreover, these biomarkers showed a strong ability to differentiate the two clinical groups. Interestingly, neoadjuvant treatment (NT) seemed to reduce NETosis biomarkers mainly systemically (plasma) compared to the tumor environment (PF). In conclusion, NETosis biomarkers are present in the tumor environment of patients with advanced HGSOC, which might contribute to the progression of the disease. Besides, plasma cfDNA and calprotectin could represent minimally invasive surrogate biomarkers for HGSOC. Finally, NT modifies NETosis biomarkers levels mainly at the systemic level.